Determining the effectiveness of Candida guilliermondii in the biological control of Rhizopus stolonifer in postharvest tomatoes - Celis Zambrano, Crispin; Javeriana University (2013)
Post-harvest losses in tomato crops can be accredited to a number of causes, which include biological causes that produce physiological deterioration; infection caused by diseases and pests that cause rotting. In this study, we assayed, in vitro and in vivo, the yeast Candida guilliermondii to determine its effectiveness as a biocontrol to reduce the rotting produced by Rhizopus stolonifer on tomatoes (Lycopersicon esculentum). The antagonistic effect was tested using a yeast biomass suspension; gas chromatography and a mass selective detector were used to identify its metabolites. According to the in vitro test, the only phase with an antagonistic response against Rhizopus stolonifer was the unfiltered water phase. In the in vivo tests, the biomass of Candida guilliermondii presented the highest percentage of protection of the tomato (87 %) compared with the unfiltered aqueous phase and the unconcentrated organic phase, which reached only 77 and 80 % respectively. These results are essential to avoid economic losses caused by fungi and to increase the shelf life of tomatoes improving the distribution of the product and preventing postharvest losses in this time of food crises, especially in developing countries.